Location Awareness Dissemination via MANET - Ku Khalif, Ku Muhammad Zahid (Universiti Teknologi Petronas, 2011)
The purpose of this research is to study on Mobile Ad Hoc Networks (MANETs) that can be used as awareness dissemination for road users. The first phase of the project involves a study on the project area where we identify ad hoc network as medium and the main study in developing this project. We also use Android apps as a simulation in generating the output. The final phase involves implementing the system physically on both real mobile and static nodes. The aspects explored are the capabilities and consistency required to be successful in the notifying and disseminating message, the environment that driver in, the car vs. the road identity that is shown through the general appearance of the driver, and the values in cultivating awareness among road users. We are finding that simple and user-friendly interface application does help a lot for road users; we hope to find how one enhances their danger awareness around them.